The association between transforming growth factor beta1 polymorphism and susceptibility to pulmonary fibrosis: A meta-analysis (MOOSE compliant). Issue 37 (September 2018) - Xin, Lili; Jiang, Miao; Su, Guangbao; Xie, Miao; Chen, Hui; Liu, Xiao; Xu, Muge; Zhang, Geng; Gong, Jiening
Abstract : Abstract: Although many studies have investigated the association of single nucleotide polymorphisms (SNPs) in transforming growth factor beta1 (TGF-β1) gene with pulmonary fibrosis (PF), but their association is still controversial. To clarify this, we performed a meta-analysis. Studies related to TGF-β1 and PF were retrieved from PubMed, Medline, Embase, Scopus, and Wanfang (up to November 30, 2017). We targeted TGF-β1 SNPs that have been reported by ≥3 studies to be included in the current meta-analysis, resulting in only 1 final SNP (rs1800470). The odds ratios (ORs) and 95% confidence intervals (CIs) were estimated in the models of allele comparison (T vs C), homozygote comparison (TT vs CC), dominant (TT vs TC + CC), recessive (TT + TC vs CC) to evaluate the strength of the associations. A total of 7 case-control studies were included in this meta-analysis. Overall, no significant association between TGF-β1 rs1800470 and PF was found (T vs C: OR [95% CI] = 0.96 [0.80, 1.15]; TT vs CC: 0.87 [0.61, 1.22]; TT vs TC + CC: 0.80 [0.62, 1.04]; TT + TC vs CC: 1.13 [0.83, 1.54]). In subgroup analyses by ethnicity or original disease, no statistically significant association between TGF-β1 rs1800470 polymorphisms and PF was demonstrated. This meta-analysis revealed that TGF-β1 rs1800470 polymorphism was not associated with susceptibility to PF development.